MEASURING THE FINANCIAL ILLUSION IN IRAQ BY USING AUTOREGRESSIVE MODELS - Hashim jabbar Hussein (Scholar Express Journals, 2025)
This research aims to analyze the phenomenon of financial illusion in the Iraqi economy by applying autoregressive models, particularly the VECM (structural error correction model), based on quarterly economic data spanning the years 2005 to 2024. The study examined the difference between nominal and real income as a primary indicator of financial illusion, taking into account the impact of inflation rates and expectations, the exchange rate, consumer spending, and savings. The results of the Extended Dickey-Fuller (ADF) test showed that all variables were stationary at the first level, which enabled the use of Johansen cointegration tests, which revealed the existence of long-run relationships between the variables. The VECM model confirmed the presence of self-correcting forces that restore balance between economic variables in the event of temporary deviations. The study also revealed the weakness of the tax and institutional structure in Iraq, the presence of a clear imbalance in revenue collection and expenditure allocation, and the prevalence of financial corruption and misuse of resources, which have contributed to deepening the illusion of economic growth among members of society. The study concluded that financial illusion is a phenomenon that influences the behavior of consumers and decision-makers alike. It called for structural reforms that enhance transparency, adopt modern digital systems, and enhance oversight of public revenues and expenditures, in addition to promoting financial literacy among citizens to mitigate the impact of misperceptions of the economic reality
Keywords: Financial Illusion; VECM; autoregressive models